EVALUASI PROGRAM PENYULUHAN PERTANIAN DAN PENGARUH FAKTOR SOSIAL EKONOMI TERHADAP PENDAPATAN PETANI PADI SAWAH - Muhammad Thamrin; Hadriman Khair; Ade Ryantika (AGRIUM: Jurnal Ilmu Pertanian, 2011)
AbstractThe results of research using descriptive analysis shows that the agricultural extension program in Medan Krio Kecamatan Sunggal BPP is Legowo 4:1 cropping system, establishment of Gapoktan, Integrated Crop Management Field School (SLPTT), RDKK Subsidized Fertilizer and Agribusiness Program Rural (PUAP). While the research results obtained using multiple linear regression that simultaneously socioeconomic factors, education, experience, area and number of dependents are able to explain changes in income of paddy farmers at 99%. Partial factors of education and area of land affected by the real-value t count> t-table and the experience factor and the number of dependents does not affect real with t-values calculated <t-table on the  income of paddy farmers at 95% confidence level (a=5%). Key Words : Agricultural Extension Program, Income Farmers Rice